2008
DOI: 10.1596/1813-9450-4722
|View full text |Cite
|
Sign up to set email alerts
|

Promotion With And Without Learning: Effects On Student Enrollment And Dropout Behavior

Abstract: Many educators and policymakers have argued for lenient grade promotion policy --even automatic promotion --in developing country settings where grade retention rates are high. The argument assumes that grade retention discourages persistence or continuation in school and that the promotion of children with lower achievement does not hamper their ability or their peer's ability to perform at the next level. Alternatively, promoting students into grades for which they are not prepared may lead to early dropout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
1
18
0
3
Order By: Relevance
“…The effect of AP on student dropout was also assessed in Pakistan's primary education by King et al (1999), and Chohan & Qadir (2011). While Chohan & Qadir (2011) employed qualitative research approach, King et al (1999) employed quantitative research design.…”
Section: Ap and Student Dropoutmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of AP on student dropout was also assessed in Pakistan's primary education by King et al (1999), and Chohan & Qadir (2011). While Chohan & Qadir (2011) employed qualitative research approach, King et al (1999) employed quantitative research design.…”
Section: Ap and Student Dropoutmentioning
confidence: 99%
“…While Chohan & Qadir (2011) employed qualitative research approach, King et al (1999) employed quantitative research design. Chohan & Qadir (2011) found that teachers consistently promoted students to save them from dropping out of the education system.…”
Section: Ap and Student Dropoutmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, grade retention is viewed as leading to an improvement in cognitive learning outcomes (Brophy, 2006;Roderick et al, 2002;and King et al, 1999). It is worth noting that studies that have reported academic gains attributable to repetition have gone on to add that the gains are short-term and as a result eventually retained students end up lagging behind, which affects their self-esteem and increases the probability of dropping out (Brophy, 2006;and Jimerson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%